The Benefits, Challenges and Impacts of Telehealth Student Clinical Placements for Accredited Health Programs During the COVID-19 Pandemic - Bacon, Rachel; Hopkins, Sian; Kellett, Jane; Millar, CaraJane; Smillie, Linda; Sutherland, Rebecca (Frontiers in Medicine, 2022)
Introduction Despite the advantages of telehealth, there has been a reluctance in its widespread adoption. During the COVID-19 pandemic, telehealth services and related placements increased internationally. Yet, there is currently limited research on the use of telehealth for student clinical placements. Aim To explore the perceived benefits, challenges, and impacts of telehealth placements for key stakeholders (clients, students, clinical educators, and placement co-ordinators) in allied health courses. Methods Stakeholder experiences with telehealth placements, undertaken within an Australian Allied Health University Clinic, were explored in virtual focus groups held between November 2020 and March 2021. These discussions used semi-structured interview questions, were audiotaped and transcribed verbatim. They were then thematically analyzed independently by two researchers, then cross-checked for consistency, using a qualitative descriptive approach, with reflexivity applied. Results Twenty-six stakeholders from six allied health disciplines participated in seven homogeneous focus groups. Three themes were identified: (1) telehealth placements support competency development and graduate employability; (2) telehealth placements enable students to provide person centered-care; and (3) telehealth placements enabled innovation. Conclusion Telehealth placements can make a valuable contribution as part of an overall placement program within accredited health courses and offer distinct advantages to student learning outcomes.